2016
DOI: 10.1002/ajmg.a.37761
|View full text |Cite
|
Sign up to set email alerts
|

Establishing SON in 21q22.11 as a cause a new syndromic form of intellectual disability: Possible contribution to Braddock–Carey syndrome phenotype

Abstract: A recent study of exome analyses in 109 patients with undiagnosed diseases included a 5-year-old girl with intellectual disability and multiple congenital anomalies, who had an apparently de novo frameshift mutation in SON. However, the combination of the truncating mutation in SON and the phenotype has not been reproduced until date, and it remains unclear if this combination represents a distinctive disease entity. Here we report an additional male with intellectual disability, congenital heart disease, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 9 publications
3
55
0
Order By: Relevance
“…3a). The former is derived from a SON mutation reported by Kim et al [1], and the latter is from the most prevalent mutation found in ZTTK syndrome [1,3,4]. The effective production of hSONr, hSONm1, and hSONm2 in HEK293 cells in the presence of shRNA#1 was con rmed (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…3a). The former is derived from a SON mutation reported by Kim et al [1], and the latter is from the most prevalent mutation found in ZTTK syndrome [1,3,4]. The effective production of hSONr, hSONm1, and hSONm2 in HEK293 cells in the presence of shRNA#1 was con rmed (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Recent genetic studies identi ed 31 individuals exhibiting intellectual disability (ID) and/or developmental delay with de novo heterozygous mutations in SON, which was established as Zhu-Tokita-Takenouchi-Kim (ZTTK) syndrome [1][2][3][4][5][6]. ZTTK syndrome was further characterized as a congenital anomaly syndrome of ID, brain malformation, facial dysmorphism, musculoskeletal abnormalities, and less common visceral malformations [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient had an apparently de novo frameshift mutation in SON , which is located within the critical region for Braddock–Carey syndrome. Although pinpointing the cause of the intellectual disability is difficult, taking into consideration the prior report of a patient with a similar phenotype and the same frameshift mutation in SON [Zhu et al, ], we suggest that the developmental delay observed in Braddock–Carey syndrome may be attributable to haploinsufficiency of SON [Takenouchi et al, ]. Because Braddock–Carey syndrome is a contiguous gene syndrome in 21q22, genes other than SON could contribute to its overall phenotype.…”
mentioning
confidence: 78%
“…ZTTK syndrome was further characterized as a congenital anomaly syndrome of ID, brain malformation, facial dysmorphism, musculoskeletal abnormalities, and less common visceral malformations [1,2,4]. The mutations found to be associated with ZTTK syndrome are mostly frameshift mutations and nonsense substitutions generating a premature termination codon [1][2][3][4][5][6], and transcripts of the mutant gene seem to be degraded due to nonsense-mediated mRNA decay (NMD) [1]; this has made ZTTK syndrome to be regarded as an entity caused by SON haploinsufficiency.…”
Section: Introductionmentioning
confidence: 99%